Performance-based design of 100% recycled hot-mix asphalt and validation using traffic load simulator. (10th November 2019) - Zaumanis, M.; Arraigada, M.; Wyss, S.A.; Zeyer, K.; Cavalli, M.C.; Poulikakos, L.D.
Abstract: This paper reports a comprehensive study on application of performance-based design method for design of 100% recycled asphalt wearing course mixture and demonstrates the performance of the optimum composition from mechanical, traffic safety and environmental points of view. An AC8 type mixture was designed by balancing performance in rutting using French rut tester and cracking using semi-circular bend test. Five iterations of different grading and binder content combinations of 100% RAP mixture were tested before achieving the same performance as a traditional AC8 mixture. This optimum mixture design was then validated by producing asphalt slabs for testing using a Model Mobile Load Simulator (MMLS3). Digital image correlation results of the wheel loading demonstrated that performance-optimized 100% recycled asphalt can sustain 2.5 times more load applications compared to the traditional mixture before cracking. This wearing course recycled asphalt mixture was then tested for skid resistance and particle abrasion due to rolling tires and achieved similar results to the reference mixture. The research allows concluding that the proposed mixture design approach can be successfully applied for designing 100% recycled asphalt mixtures that perform similar or better than traditional wearing course asphalt mixtures in all key domains and are safe to the traffic and the environment. Graphical abstract: Image 1 Highlights: Performance-based tests allows designing 100% recycled asphalt mixtures 100% RAP sustains twice as many wheel passes in traffic simulator than reference Surface abrasion of recycled asphalt is very low and smaller than of virgin asphalt 100% recycled asphalt can not be designed using traditional methods Flexibility Index is a good candidate for performance-based specification